Membranas de acetato de celulose derivadas de biomassa e modificadas com TiO2/óxido de grafeno para tratamento de emulsões de petróleo em água - Schmidt, Djanyna Voegel de Carvalho (2024)
Considering the environmental impact and health risks caused by oily wastewater in the petrochemical industry, it is crucial to develop more efficient separation techniques than traditional methods, such as membrane separation, for treating stable emulsions enriched with natural surfactants. This study investigated the preparation of dense cellulose acetate membranes from a low-cost biomass precursor (Luffa cylindrica) and their modification with graphene oxide and TiO2 nanoparticles, aiming to obtain a polymeric nanocomposite with good flow characteristics and selectivity for the treatment of oil/water emulsions. The obtained materials were characterized using techniques such as X-ray diffraction, nuclear magnetic resonance spectroscopy, and infrared absorption spectroscopy, along with optical and scanning electron microscopy, among others. The results revealed cellulose with a crystallinity index of 83%, cellulose triacetate with a degree of acetylation of 2.64 and a molar mass of 38,722 g/mol, as well as graphene oxide with a high degree of oxidation and graphene oxide modified with TiO2 in its anatase form. The membranes were prepared using the phase inversion technique and modified with the mentioned nanostructured materials. Microscopy analyses revealed that the membranes with the addition of graphene oxide functionalized with TiO2 showed better interaction with the cellulose acetate matrix. The flow and rejection analyses with oil emulsion revealed that the cellulose acetate membrane exhibited 63% oil rejection but faced fouling issues. Membranes modified with graphene oxide improved flow, but selectivity was compromised due to lower compatibility of the material with the cellulose acetate matrix. Membranes modified with graphene oxide and TiO2 nanoparticles showed significant improvements in fouling resistance compared to unmodified membranes and those modified with graphene oxide. These enhanced properties highlight the potential of modified cellulose acetate membranes for application in industrial wastewater treatment.